2020
DOI: 10.3390/jcm9082367
|View full text |Cite
|
Sign up to set email alerts
|

Real-Life Incident Atrial Fibrillation in Outpatients with Coronary Artery Disease

Abstract: Background: The risk, correlates, and consequences of incident atrial fibrillation (AF) in patients with chronic coronary artery disease (CAD) are largely unknown. Methods and results: We analyzed incident AF during a 3-year follow-up in 5031 CAD outpatients included in the prospective multicenter CARDIONOR registry and with no history of AF at baseline. Incident AF occurred in 266 patients (3-year cumulative incidence: 4.7% (95% confidence interval (CI): 4.1 to 5.3)). Incident AF was diagnosed during cardiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…The risk factors for AF are well established and include hypertension, heart failure (HF), physical activity, obesity, chronic coronary syndromes, chronic kidney disease (CKD), and hyperthyroidism [ 1 , 2 , 3 , 4 ]. The determination of risk factors is particularly important in patients with silent atrial fibrillation (SAF), but their identification is a challenge in everyday clinical practice and, often, such patients are diagnosed for the first time when they present with an AF-related complication, such as stroke or heart failure; however, general population-based data for silent AF (SAF) are limited.…”
Section: Introductionmentioning
confidence: 99%
“…The risk factors for AF are well established and include hypertension, heart failure (HF), physical activity, obesity, chronic coronary syndromes, chronic kidney disease (CKD), and hyperthyroidism [ 1 , 2 , 3 , 4 ]. The determination of risk factors is particularly important in patients with silent atrial fibrillation (SAF), but their identification is a challenge in everyday clinical practice and, often, such patients are diagnosed for the first time when they present with an AF-related complication, such as stroke or heart failure; however, general population-based data for silent AF (SAF) are limited.…”
Section: Introductionmentioning
confidence: 99%
“…This is also reflected in research; studies would look at the association of individual risk factors and comorbidities with incident AF. [2][3][4][5][6] However, individuals with AF commonly have more than one comorbidity and thus multimorbidity. 1 16-18 This study has shown that latent class analysis can be used to define clusters of comorbidities, but that the clusters seem to be based on the amount of comorbidities, rather than specific combinations of comorbidities.…”
Section: Arrhythmias and Sudden Deathmentioning
confidence: 99%
“…1 Presence of specific cardiovascular risk factors and/ or comorbidities increase the risk of incident AF. [2][3][4][5][6] Both the prevalence of AF and of comorbidities increase with age, causing the prevalence of multimorbidity (the presence of two or more comorbidities in an individual) to increase as well. [7][8][9][10][11] With the accumulation of comorbidities over time, certain comorbidities may more often occur together than others, that is, clustering of comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of AF pathophysiology could come from the integration of all the cardiac environment modulators, including "Coumel triangle" components [3]. Indeed, apart from the pulmonary vein triggers that have been extensively studied [4], the relationship between other triggers (inflammation as in acute AF [5][6][7], stable coronary artery disease [8], or post-operative AF [9]), the modulator (mainly autonomic nervous system dysregulation [10]) and substrate alterations (fibrosis but also changes in the conduction properties of the atrial cells even in the absence of a quantifiable "scar" [11]) have been recently brought to light by several papers [12,13]. The interplay between cardiovascular risk factors, mainly high blood pressure [14] and obesity [6], atrial epicardial fat, and atrial ganglionated plexi [15], is complex and critical for the understanding of AF, but also in the search for new treatments.…”
mentioning
confidence: 99%